Whistle-Blowing - Kaur, Harsh Vineet (Prabandhan: Indian Journal of Management, 2009)
The term whistleblower derives from the practice of English bobbies who would blow their whistle when they noticed the commission of a crime. The blowing of the whistle would alert both law enforcement officers and the general public of the danger. A whistleblower is an employee, former employee, or member of an organization, especially a business or government agency, who reports misconduct to people or entities that have the power and presumed willingness to take corrective action. Generally the misconduct is a violation of law, rule, regulation and/or a direct threat to public interest, such as fraud, health/safety violations, and corruption. Whistle-blower meaning he exposes wrongdoing, fraud or inefficiency in his or her workplace, where one is not supposed to.